-7(6x+5)=-7x+14

Simple and best practice solution for -7(6x+5)=-7x+14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(6x+5)=-7x+14 equation:


Simplifying
-7(6x + 5) = -7x + 14

Reorder the terms:
-7(5 + 6x) = -7x + 14
(5 * -7 + 6x * -7) = -7x + 14
(-35 + -42x) = -7x + 14

Reorder the terms:
-35 + -42x = 14 + -7x

Solving
-35 + -42x = 14 + -7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7x' to each side of the equation.
-35 + -42x + 7x = 14 + -7x + 7x

Combine like terms: -42x + 7x = -35x
-35 + -35x = 14 + -7x + 7x

Combine like terms: -7x + 7x = 0
-35 + -35x = 14 + 0
-35 + -35x = 14

Add '35' to each side of the equation.
-35 + 35 + -35x = 14 + 35

Combine like terms: -35 + 35 = 0
0 + -35x = 14 + 35
-35x = 14 + 35

Combine like terms: 14 + 35 = 49
-35x = 49

Divide each side by '-35'.
x = -1.4

Simplifying
x = -1.4

See similar equations:

| 0=00m | | 1,340,000,000,000i=23 | | -15=-1.5m | | (2x-4y+6)dx=(3-x-y)dy | | 3tan^2x+4=5 | | (6)(3i+4)(1)+(4y+1)(2i)=(8iy+2i)+(18i+24) | | 19x+13y=7 | | -8x+4y=-12 | | 15-d=8 | | 0.045x-5/8y=120 | | x^8-26x+25=0 | | 2x+14i=1 | | (x^3+3x^2-16x-48)=0 | | -37+46.98-(-0.02)= | | 5s-(100+2s)=0 | | 3(10-6)(3-7)= | | 55m-139m-64m= | | 8x^6/6x^3 | | ln(x-3)=1.4 | | x-9(2/3x-6)=30 | | 1/2z=9/4 | | -5/13x=-8 | | 5m-139m-64m= | | 10m^3n^3-2mn^2+14mn= | | x+y-3z=-7 | | -9+8x=7x+15 | | 5(x+8)-6=44 | | 8x^2-28x+2x-7=.5 | | 5849=3.14x*81 | | 11w=132 | | -30=x+12 | | 17.8-(-4.006)-22= |

Equations solver categories